Audit committee compensation, best practices and audit fees - Bum-Jin Park (South African Journal of Business Management, 2019)
Background: It is extremely important that an audit committee (AC) monitors a company’s financial reporting process, and that the committee engages a high-quality auditor to carry this out effectively. Prior research on ACs has paid much attention to the relationship between AC best practices and audit fees (AF). Although compensation is a means of aligning interests between ACs and stakeholders, previous studies have neglected the complementary interaction between AC compensation and compliance with best practices on audit quality.